Radiological and functional outcome of talus fracture in local population: Our experience in Government tertiary care trauma center. - Farhan Sozera; Faheem Ahmed Abbasi; Syed Akmal Sultan; Affan Tayyab; Mehmood, Raza (International Journal of Endorsing Health Science Research, 2024)
Background: Talus fractures pose significant challenges in orthopedic management, particularly in lower socioeconomic populations. Open Reduction and Internal Fixation (ORIF) is a commonly employed surgical approach to restore joint congruity and function. However, outcomes in such populations may be influenced by factors like access to healthcare and postoperative rehabilitation. This retrospective study aimed to evaluate the radiological and functional outcomes of talus fractures treated with ORIF in a lower socioeconomic class population. Methodology: The study was conducted at a Tertiary Care Trauma Centre and involved 11 patients aged 18-25. Preoperative planning included X-rays and 3-dimensional Computed Tomograms (CT Scans) of the ankle joint. Surgical approaches included the standard medial approach, a dual approach, and an approach with medial malleolus osteotomy. Functional outcomes were assessed using the American Orthopedic Functional Ankle Scoring (AOFAS). Radiological outcomes were evaluated through postoperative X-rays, with reduction considered satisfactory if < 2 mm joint step was achieved. Incidence of avascular necrosis of the Talus (ANT), post-traumatic arthritis (PTA), and other complications were analyzed. Results: With a mean follow-up of 18 months, concentric reduction was achieved in 85% of cases. Postoperative complications included PTA of the subtalar joint in 45.4% of patients, PTA of the ankle joint in 20%, Avascular Necrosis (AVN) in 18.1%, delayed union in 9%, and surgical site infection (SSI) in 9%. Conclusion: Despite advancements, talus fractures treated with ORIF remain challenging, especially in lower socioeconomic populations. High complication rates highlight the importance of meticulous surgical planning and postoperative management. Nonetheless, ORIF offers acceptable functional outcomes and facilitates early return to work in these patients.